2021
DOI: 10.3390/molecules26030674
|View full text |Cite
|
Sign up to set email alerts
|

Computational Determination of Potential Multiprotein Targeting Natural Compounds for Rational Drug Design Against SARS-COV-2

Abstract: SARS-CoV-2 caused the current COVID-19 pandemic and there is an urgent need to explore effective therapeutics that can inhibit enzymes that are imperative in virus reproduction. To this end, we computationally investigated the MPD3 phytochemical database along with the pool of reported natural antiviral compounds with potential to be used as anti-SARS-CoV-2. The docking results demonstrated glycyrrhizin followed by azadirachtanin, mycophenolic acid, kushenol-w and 6-azauridine, as potential candidates. Glycyrr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 97 publications
1
18
0
Order By: Relevance
“…However, and despite the huge number of research studies reported so far, the development of safe and effective drugs able to block the viral infection is still lacking and represents a major goal for the scientific world. Among all the possible chemical compounds, particular attention has been dedicated to molecules of natural origin [5][6][7][8], including extracts, single bioactive molecules, or entire classes of phytochemicals targeting SARS-CoV-2, and several of them are currently under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…However, and despite the huge number of research studies reported so far, the development of safe and effective drugs able to block the viral infection is still lacking and represents a major goal for the scientific world. Among all the possible chemical compounds, particular attention has been dedicated to molecules of natural origin [5][6][7][8], including extracts, single bioactive molecules, or entire classes of phytochemicals targeting SARS-CoV-2, and several of them are currently under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Alamri et al utilized molecular docking and dynamic simulations to identify M pro candidates from Saudi medical plants 20 . Muhseen et al used the above two methods to identify M pro inhibitors from MPD3 phytochemical database 21 24 . Certain database-specific inhibitors search were also made including Super Natural II 25 , Marine Natural Product (MNP) 26 and Traditional Chinese Medicine 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Mycophenolic acid is also an immunosuppressive drug with a strong anti-proliferation effect (Kim et al, 2019). Studies suggest that mycophenolic acid has a potential inhibitory effect on the enzyme reproduced by SARS-CoV-2 (Muhseen et al, 2021).…”
Section: Case Studymentioning
confidence: 99%